Decoding Demise: A Comprehensive Analysis of Unnatural Deaths in Rahim Yar Khan: Decoding Demise: A Comprehensive Analysis of Unnatural Deaths - Kamran, Qurrat-ul-Ain; Munir, Ummara; Pal, Mobin Inaam; Samad, Abdul; Imran, Shahla; Ali, Mashooq (Pakistan Journal of Health Sciences, 2024)
A medico-legal autopsy is a systematic examination of a deceased body conducted under the law of the state to determine the cause, and manner of death and to verify or dismiss any potential involvement of foul play related to the deceased. Objective: To assess the spectrum of unnatural deaths in the district of Rahim Yar Khan. Methods: This retrospective descriptive study was done at the Department of Forensic Medicine and Toxicology, Sheikh Zayed Medical College, Rahim Yar Khan from 1st January 2021 to 31st December 2023. Variables were age, gender, cause and manner of death, weapon, and residence. All autopsies referred by police were included except hospital, police torture and custodial deaths, and putrefied or exhumed bodies. Data from police, hospital records, and autopsy reports were recorded on a pre-designed form. Results: There was male preponderance of 72.57% to female with 27.43%. In general, 78% of all deaths were homicidal, compared to 12% suicidal, 9% accidental and 1% remained undetermined. The 21-30-year age range is the most often afflicted group. Firearms as the leading cause of death followed by blunt objects, asphyxia and sharp weapons accounted for the majority of fatalities respectively. The instances involved 44.25 % urban inhabitants as compared to 55.75% peri-urban ones. Conclusions: It was concluded that men accounted for the majority of unnatural deaths. The most common cause of death was murder. Guns and blunt weapons were the leading causes of death. Compared to the surrounding area, the city had a higher number of unnatural fatalities.